Analisis Pengaruh Growsal, Firm size, Profitabilitas, terhadap Struktur Modal - Novadilastri, Novadilastri; Gustati, Gustati; Wira, Variyetmi; Chandra, Benny (Jurnal Kajian Manajemen Bisnis, 2014)
Consumer goods industry is an industry that is engaged in a business that meets the needs of human life. To run the activities of the company, the company has a policy in the use of sources of funds, especially debt. Capital structure is the composition of debt and equity capital. The purpose of the study was to observe the effect of sales growth, firm size and the profitability of the company on the capital structure. This study used a sample of consumer goods companies listed in Indonesia Stock Exchange from 2009 to 2011. The method used is regression using SPSS for windows version 19. The result Â showed that in the consumer goods industry, the three variables (sales growth, firm sizeÂ  and profitability) simultaneously statistically proven not affect the capital structure. Partial test showed significance greater than 5%. This means that the three variables (sales growth, firm size and profitability was also not statistically proven to affect the capital structure during the period 2009 to 2011 in consumer goods industry.